Mangrove leaf species-specific isotopic signatures along a salinity and phosphorus soil fertility gradients in a subtropical estuary. (5th January 2021) - He, Ding; Rivera-Monroy, Victor H.; Jaffé, Rudolf; Zhao, Xiaochen
Abstract: Mangrove ecotypes are distinct monospecific or mix-species assemblages and used as classification criteria to evaluate coastal biogeochemical cycles at the local, regional, and global scales. However, it is not clear how plant nitrogen and carbon content, including bulk δ 13 C and δ 15 N and n -alkane δ 13 C values, vary across species and within species when plants are exposed to the interaction between nutrient (nitrogen-N, phosphorus-P) availability and stressors (i.e., salinity). Here we present significant differences in green leaves wax n -alkane δ 13 C (δ 13 C n -alkane ) values and brown-senescent leaves C:N atomic ratios and total phosphorus (TP) concentrations of three mangrove species ( Rhizophora mangle, Laguncularia racemosa, and Avicennia germinans ) that reflect ecophysiological adaptations to nutrient availability and salinity along the Shark River estuary (SRE), South Florida, USA. Linear models between leaf wax δ 13 C n -alkane values and species location along TP fertility and salinity gradients showed distinct differences, particularly between the species A. germinans and R. mangle . Our analyses showed that leaf wax δ 13 C n -alkane properly represented major differences in ecophysiological responses by each mangrove species. We also found that both R. mangle and L. racemosa showed different isotopic footprints among the SRE upper, middle and lower estuarine salinity regions. Further, the green leaves bulk δ 13 C values in R. mangle (−32.3‰ to −27.6‰) were positively correlated with distance from the mouth of the estuary. In contrast, L. racemosa showed a negative relationship with distance and a narrower bulk δ 13 C range (−29.8‰ to −28.1‰) in comparison to the other two species. A. germinans, a species found only in the brackish (salinity: 18.8 ± 1.2) and saline (30.3 ± 0.53) estuarine regions, also showed a positive bulk δ 13 C relationship with distance. Because of the well-defined species-specific leaf wax n -alkane δ 13 C values along both water column/soil pore water salinity and TP gradients, we propose these values as a potential salinity proxy for paleoclimate reconstruction. Highlights: Mangrove leaves δ 13 C and δ 15 N are well-defined along soil salinity and P gradients. Rhizophora mangle and Laguncularia racemosa have distinct isotopic composition. Mangrove leaf wax n -alkane δ 13 C could be used as salinity paleoclimate proxy.